Kepatuhan Wajib Pajak UMKM dengan Sosialisasi Pajak sebagai Variabel Moderasi - Sinthia Anjelina; Diana Frederica; Deni Iskandar (Program Studi Akuntansi FPEB UPI, 2023)
This study aims to examine the effect of tax incentives and tax understanding on PMK No. 86 of 2020 on taxpayer compliance with tax socialization as a moderating variable. This study uses primary data by distributing questionnaires to owners of Micro, Small and Medium Enterprises (MSMEs) who are domiciled in West Jakarta. By using a sampling technique, namely convenience sampling, the researchers managed to collect 103 respondents from the distributed questionnaires. The data were tested using the SPSS application with multiple linear regression model analysis. From the test results that have been carried out, it can be concluded that tax incentives have no effect on taxpayer compliance, tax understanding has a positive effect on taxpayer compliance, tax socialization strengthens the effect of tax incentives on taxpayer compliance, and tax socialization weakens the effect of tax understanding on taxpayer compliance.